The criterion of relative power and the flexural-strength approach in the interpretation of the folding of a single layer - Gonchar, V. V. (Geofizicheskiy Zhurnal, 2010)
Buckling - strength approach is proposed for outline correlations between thickness and foldlength of the competent layer in naturally occurring folds, which is based on elastoplastic description of buckling in which the tangential modulus is used for nonelastic stage of deformation. Assumption of contemporary f olding of layer and destruction of medium is introduced, which allows to obtaina link between depth and foldlength with layer/medium property contrast counting. Valuation of prefold deformation is made, which is fined compareable with elastic-scale deformation of rocks. Refference thickness as a criterion of different modes of buckling against faulting-plastic mode deformation of competent layer is regarded.